Squamous Cell Carcinoma Mimicking Neck Paraganglioma on 68Ga-DOTATATE PET/CT. (July 2021) - Civan, Caner; Isik, Emine Goknur; Has Simsek, Duygu; Sen, Comert; Unal, Seher Nilgun
Abstract : Abstract: Somatostatin receptor (SSTR) imaging with 68 Ga-labeled somatostatin analogs has been used for many tumors with high SSTR expression. Increased uptake mostly depends on the SSTR status of tumors; however, false-positive uptake can be demonstrated in benign diseases or other malignancies because of the increased SSTR expression. We present a case of a 50-year-old man with increased SSTR activity on cervical lesion located in internal jugular chain in 68 Ga-DOTATATE PET/CT, which was performed for suspicion of paraganglioma. Biopsy revealed lymph node metastasis of squamous cell carcinoma other than paraganglioma. 18 F-FDG PET/CT showed primary malignancy on larynx and lymph node metastasis, which were correlated surgically.